Performance of alternative COPD case-finding tools: a systematic review and meta-analysis - Schnieders, Elena; Uenal, Elyesa; Winkler, Volker; Dambach, Peter; Louis, Valérie R.; Horstick, Olaf; Neuhann, Florian; Deckert, Andreas (European respiratory review, 2021)
Rationale Guidelines recommend pre-/post-bronchodilator spirometry for diagnosing COPD, but resource constraints limit the availability of spirometry in primary care in low- and middle-income countries. Although spirometry is the diagnostic gold standard, we shall assess alternative tools for settings without spirometry. Methods A systematic literature review and meta-analysis was conducted, utilising Cochrane, CINAHL, Google Scholar, PubMed and Web of Science (search cut-off was May 01, 2020). Published studies comparing the accuracy of diagnostic tools for COPD with post-bronchodilator spirometry were considered. Studies without sensitivity/specificity data, without a separate validation sample and outside of primary care were excluded. Sensitivity, specificity and area under the curve (AUC) were assessed. Results Of 7578 studies, 24 were included (14635 participants). Hand devices yielded a larger AUC than questionnaires. The meta-analysis included 17 studies and the overall AUC of micro-spirometers (0.84, 95% CI 0.80-0.89) was larger when compared to the COPD population screener (COPD-PS) questionnaire (0.77, 95% CI 0.63-0.85) and the COPD diagnostic questionnaire (CDQ) (0.72, 95% CI 0.64-0.78). However, only the difference between micro-spirometers and the CDQ was significant. Conclusions The CDQ and the COPD-PS questionnaire were approximately equally accurate tools. Questionnaires ensured testing of symptomatic patients, but micro-spirometers were more accurate. A combination could increase accuracy but was not evaluated in the meta-analysis.
Gesehen am 05.08.2021